Gender-Wage Gap in the Chinese Labour Market - Jiang, Wendi (Université d'Ottawa | University of Ottawa, 2018)
The gender wage gap in China is large and has been increasing during recent years. This paper uses data from the 2013 Chinese General Social Survey (CGSS) to investigate the factors that account for wage differences between males and females in China. The paper employs a regression analysis and a Blinder-Oaxaca decomposition technique to ascertain the causes of the gap between males and females. The results of the regression analysis show that there is a large gender-wage gap in the Chinese labour market. The main variables of region, education, and marital status have important effects on wages. Moreover, the Blinder-Oaxaca decomposition results show that the wage gap is entirely due to the unexplained component, sometimes called discrimination, that is, to differences in the regression coefficients between the male and female regressions.